2018
DOI: 10.22159/ajpcr.2017.v11i1.17532
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Failure Causes Osteopathy or Is Osteopathy a Factor in Development of Chronic Heart Failure?

Abstract: Objective: As their proportion rises in the aging population, cardiovascular disease and osteoporosis increasingly become significant health problems of the developed world, leading to reduced lifespan and substantial financial burdens, not the least because of complications and comorbidities associated with each disorder. This study investigates bone mineralization in patients with coronary heart disease (CHD) complicated by Stage I chronic heart failure (CHF). Methods:The study group consisted of 41 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Traditionally osteoporosis and CVD were considered unrelated and their coexistence has been attributed to independent processes exclusively related to age. However, the majority of the studies have shown that individuals with CVD have a higher risk of experiencing bone loss and thus greater predisposition to risk of fracture [4]. On the other hand there is growing evidence that individuals with low bone mass have higher mortality for cardiovascular events compared to patients with cardiovascular disease with normal bone mass [2].…”
mentioning
confidence: 99%
“…Traditionally osteoporosis and CVD were considered unrelated and their coexistence has been attributed to independent processes exclusively related to age. However, the majority of the studies have shown that individuals with CVD have a higher risk of experiencing bone loss and thus greater predisposition to risk of fracture [4]. On the other hand there is growing evidence that individuals with low bone mass have higher mortality for cardiovascular events compared to patients with cardiovascular disease with normal bone mass [2].…”
mentioning
confidence: 99%